Ministry of Trade, Industry and Investment Decree No. 417 of the Year 2014 = وزارة التجارة والصناعة والاستثمار قرار رقم 417 لسنة 2014 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic